2009
DOI: 10.7163/gpol.2009.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Heatwavesin Poland – frequency, trends and relationships with atmospheric circulation

Abstract: The daily minimum and maximum temperatures at seven Polish stations were used in an analysis of the occurrence of heatwaves in the years 1951-2006. Heatwaves were defi ned as days with temperatures exceeding selected thresholds (t max ≥25°C, t max ≥30°C, t min ≥18°C). The mean length of a wave of very warm days lasts from 2-4 days, the longest no fewer than 23 days. Waves comprising hot days and nights are shorter. The frequencies of very warm and hot days and hot nights increased in the analyzed period, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 6 publications
10
33
0
1
Order By: Relevance
“…Of the exceptionally hot summer seasons in Poznań, one should especially mention the summers of 1992, 1994, 2006 and 2015. Similar results were also obtained in other regions of Poland [42][43][44]. As Sulikowska et al [27] have shown, the summer of 2015 was exceptionally hot in Poland, especially in the southwest of the country.…”
Section: Discussionsupporting
confidence: 78%
“…Of the exceptionally hot summer seasons in Poznań, one should especially mention the summers of 1992, 1994, 2006 and 2015. Similar results were also obtained in other regions of Poland [42][43][44]. As Sulikowska et al [27] have shown, the summer of 2015 was exceptionally hot in Poland, especially in the southwest of the country.…”
Section: Discussionsupporting
confidence: 78%
“…Wibig et al (2009) have shown that the frequencies of very warm and hot days increased in the period 1951-2006, especially in the second part of this period . The analysis was performed using records from six stations in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…In Poland and Czech Republic the heat wave which occurred in 1994 was very intensive and widespread (Kysely 2002;Wibig et al 2009;Kysely 2010). A lot of attention has been devoted to the 2003 heat wave over Central-European countries (Beniston 2004;Black et al 2004;Zaitchik et al 2006), followed by another exceptional heat wave in July of 2006 in Central Europe (Kysely 2010), the heat wave in July 2010 in Eastern Europe (Barriopedro et al 2011) and the heat wave in Central Europe in August 2015 (Dong et al 2016;Duchez et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Jeszcze inaczej do rozwiązania problemu wydzielania fal upałów podszedł zespół pod kierunkiem Wibig ( 2009b ). Zamiast przyjąć sztywny minimalny czas wystę-powania warunków kryterialnych badacze określali, jak często występowały fale upałów o różnym czasie trwania.…”
Section: Dyskusjaunclassified